Development of a SETS-Based Creativity, Innovation, and Entrepreneurship Electronic Module to Improve Students' Critical Thinking Skills - Dhea Sarfita; Waspodo Tjipto Subroto; Norida Canda Sakti (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study aims to analyze the development process, feasibility, student responses, and effectiveness of the Creativity, Innovation, and Entrepreneurship (KIK) e-module based on the SETS (Science, Environment, Technology, Society) approach in improving critical thinking skills of eleventh-grade vocational high school (SMK) students in Surabaya. The research method used is Research and Development (R&D) by adopting the 4-D model (Define, Design, Develop, Disseminate) combined with True Experimental Design (Pretest-Posttest Control Group Design). The research subjects involved 232 students in five SMKs in Surabaya. Data were analyzed quantitatively through normality tests, paired sample t-tests, independent sample t-tests, and Cohen's d effect size calculations. The results of expert validation showed that the e-module was very feasible to use with a percentage of 97% from material experts, 95% from language experts, and 74% from graphic experts. Student responses confirmed high practicality with a score of 94%. An independent sample t-test showed a significant difference in critical thinking posttest scores between the experimental and control groups (p < 0.05). The average N-Gain score in the experimental class reached the